Natural Clay of Pasaman Barat Enriched by CaO of Chicken Eggshells as Catalyst for Biodiesel Production - Syukri Syukri; Kevin Septioga; Syukri Arief; Yulia Eka Putri; Mai Efdi; Upita Septiani (Bulletin of Chemical Reaction Engineering & Catalysis, 2020)
This study uses broiler chicken eggshells to enhance catalytic activity of clay obtained from Pasaman Barat (West Sumatra, Indonesia) in lab-scale biodiesel production. The eggshell is a source of calcium oxide (CaO) which operates as a catalyst when mixed with the clay (Ca-Clay). Two other catalysts were also prepared as comparisons by 1) heating the clay at 800 oC for 6 hours (P-Clay), 2) mixing the P-Clay with KOH (K-Clay). An X-ray Fluorescence (XRF) showed the elemental composition of Ca-Clay contained Ca, Si, Al, and Fe. An X-ray Diffraction (XRD) showed the formation of highly crystalline CaO in the Ca-Clay with the main peak at 2θ = 37.27o. The Fourier Transform Infra Red (FTIR) spectrum showed an absorption peak in the range of 700-900 cm-1 indicating Ca-O stretching demonstrating successful incorporation of the CaO into the clay. The catalytic activity test showed the Ca-Clay had a higher catalytic performance than P-Clay and K-Clay in terms of the yield of biodiesel produced (73%). Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).